Chemical-by-chemical and cumulative risk assessment of residential indoor exposure to semivolatile organic compounds in France. (August 2018) - Pelletier, Maud; Glorennec, Philippe; Mandin, Corinne; Le Bot, Barbara; Ramalho, Olivier; Mercier, Fabien; Bonvallot, Nathalie
Abstract: Background: The toxic effects of environmental exposure to chemicals are increasingly being studied and confirmed, notably for semivolatile organic compounds (SVOCs). These are found in many products and housing materials, from which they are emitted to indoor air, settled dust and other surfaces. Objectives: The objective of this work is to assess the human health risk posed by residential indoor exposure to 32 SVOCs, assessed in previous nationwide studies. Methods: A chemical-by-chemical risk assessment, using a hazard quotient (HQ) or excess risk (ER) method, was supplemented by a cumulative risk assessment (CRA). For CRA, a hazard index (HI) method, as well as higher tier approaches using relative potency factors (RPFs) or toxic equivalency factors (TEFs) were used for the following endpoints: neurotoxicity, reproductive toxicity, genotoxicity and immunotoxicity. Results: HQs were above 1 for 50% of French children from birth to 2 years for BDE 47, and for 5% of children for lindane and dibutyl phthalate (DBP). Corresponding hazards are reprotoxic for BDE 47 and DBP, and immunotoxic for lindane. The CRA approach provided additional information of reprotoxic risks (HI > 1) that may occur for 95% of children and for 5% of the offspring for pregnant women's exposure. The SVOCs contributing most to these risks were PCB 101 and 118, BDE 47, and DBP. The higher tier CRA approaches showed that exposure to dwellings' SVOC mixtures were of concern for 95% of children for neurotoxic compounds having effects linked with neuronal death. To a lesser extent, effects mediated by the aryl hydrocarbon receptor (AhR) or by a decrease in testosterone levels may concern 5% of children and adults. Lastly, unacceptable immunotoxic risk related to exposure to 8 indoor PCBs was also observed for 5% of children. Conclusions: In view of uncertainties related to compounds' toxicity for humans, these results justify the implementation of preventive measures, as well as the production of more standardized and comprehensive toxicological data for some compounds. Highlights: 32 indoor SVOCs were assessed for their risk on human health for 11 age groups. Both chemical-by-chemical and cumulative risk assessments were used. Unacceptable risks were revealed for a certain portion of the French population. They were due to either single chemicals or groups, and for different age groups. Risk levels and weight of evidence allowed to prioritize chemicals for prevention.